XylA and xylB overexpression as a successful strategy for improving xylose utilization and poly-3-hydroxybutyrate production in Burkholderia sacchari. (1st March 2018) - Guamán, Linda P; Oliveira-Filho, Edmar R; Barba-Ostria, Carlos; Gomez, José G C; Taciro, Marilda K; da Silva, Luiziana Ferreira
Abstract: Despite the versatility and many advantages of polyhydroxyalkanoates as petroleum-based plastic substitutes, their higher production cost compared to petroleum-based polymers has historically limited their large-scale production. One appealing approach to reducing production costs is to employ less expensive, renewable feedstocks. Xylose, for example is an abundant and inexpensive carbon source derived from hemicellulosic residues abundant in agro-industrial waste (sugarcane bagasse hemicellulosic hydrolysates). In this work, the production of poly-3-hydroxybutyrate P(3HB) from xylose was studied to develop technologies for conversion of agro-industrial waste into high-value chemicals and biopolymers. Specifically, this work elucidates the organization of the xylose assimilation operon of Burkholderia sacchari, a non-model bacterium with high capacity for P(3HB) accumulation. Overexpression of endogenous xylose isomerase and xylulokinase genes was successfully assessed, improving both specific growth rate and P(3HB) production. Compared to control strain (harboring pBBR1MCS-2), xylose utilization in the engineered strain was substantially improved with 25% increase in specific growth rate, 34% increase in P(3HB) production, and the highest P(3HB) yield from xylose reported to date for B. sacchari ( Y  P3HB/Xil  = 0.35 g/g). This study highlights that xylA and xylB overexpression is an effective strategy to improve xylose utilization and P(3HB) production in B. sacchari .